Systemic signs of neutrophil mobilization during clinically stable periods and during exacerbations in smokers with obstructive pulmonary disease - Andelid, Kristina (Int J Chron Obstruct Pulmon Dis, 2015)
BACKGROUND: It is still unclear whether signs of neutrophil mobilization in the blood of patients with chronic obstructive pulmonary disease represent true systemic events and how these relate to bacterial colonization in the airways. In this study, we evaluated these issues during clinically stable periods and during exacerbations in smokers with obstructive pulmonary disease and chronic bronchitis (OPD-CB). METHODS: Over a period of 60 weeks for each subject, blood samples were repeatedly collected from 60 smokers with OPD-CB during clinically stable periods, as well as during and after exacerbations. Myeloperoxidase (MPO) and neutrophil elastase (NE) protein and mRNA, growth of bacteria in sputum, and clinical parameters were analyzed. Ten asymptomatic smokers and ten never-smokers were included as controls. RESULTS: We found that, during clinically stable periods, neutrophil and NE protein concentrations were increased in smokers with OPD-CB and in the asymptomatic smokers when compared with never-smokers. During exacerbations, neutrophil and MPO protein concentrations were further increased in smokers with OPD-CB, without a detectable increase in the corresponding mRNA during exacerbations. However, MPO and NE protein and mRNA displayed positive correlations. During exacerbations, only increased neutrophil concentrations were associated with growth of bacteria in sputum. Among patients with low transcutaneous oxygen saturation during exacerbations, PaO(2) (partial oxygen pressure) correlated with concentrations of MPO and NE protein and neutrophils in a negative manner. CONCLUSION: There are signs of systemic neutrophil mobilization during clinically stable periods and even more so during exacerbations in chronic obstructive pulmonary disease. In this condition, MPO and NE may share a cellular origin, but its location remains uncertain. Factors other than local bacteria, including hypoxemia, may be important for driving systemic signs of neutrophil mobilization.